Composition effects on mechanical properties of pristine sodium borosilicate glass. (22nd November 2018) - Zhao, Yan; Zhang, Xiaoyang; Yuan, Wei; Liu, Fengfei; Sun, Mengli; Peng, Haibo; Wang, Tieshan
Abstract: Sodium borosilicate (NBS) glass is widely used in the disposal of high level nuclear waste nowadays. In order to understand the mechanism of hardness in NBS glass varies with various compositions, nanoindentation experiment and molecular dynamics simulation were carried out. Both experimental and calculated results suggested that, the hardness of glass increased with the ratio of R ([Na2 O]/[B2 O3 ] in molar percentage) and K ([SiO2 ]/[B2 O3 ] in molar percentage). In the process of hardness increase, the [BO3 ] units were transformed into [BO4 ] units, which could lead to the polymerization increase for the glass system, and the transformation was linear to R . The hardness increase was also accompanying with the increase of silica content, which is another cause for polymerization increase. There are many possible factors that may affect the mechanical properties of pristine NBS glass, and polymerization increase should be the main reason for hardness increase, which could be resulted from the two processes above: (a) the transformation of [BO3 ] into [BO4 ]; (b) silica content increase.